Spirituality and contextuality - Waaijman, K. (Acta Theologica, 2006)
This article discusses various historiographies of spirituality as an indication of the influence of context on spirituality. It gives an overview of the most important historiographies of spirituality. Secondly, it describes the extremes of contextuality and noncontextuality, before finally reflecting on the dialectic tension between spirituality and contextuality.